Hubungan Tingkat Stress dengan Kadar Gula Darah Pada Penderita Diabetes Melitus di Puskesmas Mulyorejo Surabaya: Correlation of stress with blood glucose level in diabetes mellitus patients at Mulyorejo public health center Surabaya - Rini Hamsidi; Dwi Setiani Sumardiko; Myrna Adianti; Maya Septriana; Edith Frederika Puruhito; Ario Imandiri (Fakultas Farmasi Universitas Halu Oleo, 2023)
One of the generative diseases today increasing in numbers worldwide is diabetes mellitus (DM). In many cases, diabetic patients have higher levels even after taking regular medication. This research analyzes the correlation between stress and blood glucose levels in DM in Mulyorejo public health center Surabaya. The type of this research used a cross-sectional analysis, with the population taken from DM patients. There are 40 persons with samples of 36 respondents, a sampling technique that used simple random sampling. This instrument used a questionnaire and observation sheet, data analysis using Rank Spearmen Test with significant level α =0,05. The result of the Rank Spearmen Test gained p < α that is 0,000 < 0,05 mean there is a correlation between stress level with blood glucose level in diabetes mellitus in Mulyorejo public health center Surabaya. This research concludes that stress also influences the blood glucose level of DM. In this case, the study suggests that the DM patient can control a healthy lifestyle and avoid stress, anticipating DM symptoms and increasing blood glucose levels early. Health personnel hopes to improve motivation and inform DM patients well.